2016
DOI: 10.1016/j.phytochem.2016.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of plant secondary metabolism and associated specialized cell development by MYBs and bHLHs

Abstract: Plants are unrivaled in the natural world in both the number and complexity of secondary metabolites they produce, and the ubiquitous phenylpropanoids and the lineage-specific glucosinolates represent two such large and chemically diverse groups. Advances in genome-enabled biochemistry and metabolomic technologies have greatly increased the understanding of their metabolic networks in diverse plant species. There also has been some progress in elucidating the gene regulatory networks that are key to their synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
91
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(94 citation statements)
references
References 228 publications
(289 reference statements)
1
91
0
2
Order By: Relevance
“…The benefits of CTs have been demonstrated in only support the primary plant metabolism (Haslam, 1981). It is now well established that CT synthesis is under genetic control (Szczyglowski and Stougaard, 2008;Scioneaux et al, 2011;Cheynier et al, 2013;Escaray et al, 2014) and that expression depends on the plant species and plant parts (Larkin et al, 1997;Gebrehiwot et al, 2002;Abeynayake et al, 2012;Ferreyra et al, 2012;Hancock et al, 2012;Verdier et al, 2012;Cheynier et al, 2013;Harding et al, 2013;Mouradov and Spangenberg, 2014;Pérez-Díaz et al, 2014;Zhou et al, 2015;Zhu et al, 2015;Chezem and Clay, 2016).…”
Section: Roles Of Tannins In Plants and Challenges To Harnessing Theimentioning
confidence: 99%
See 1 more Smart Citation
“…The benefits of CTs have been demonstrated in only support the primary plant metabolism (Haslam, 1981). It is now well established that CT synthesis is under genetic control (Szczyglowski and Stougaard, 2008;Scioneaux et al, 2011;Cheynier et al, 2013;Escaray et al, 2014) and that expression depends on the plant species and plant parts (Larkin et al, 1997;Gebrehiwot et al, 2002;Abeynayake et al, 2012;Ferreyra et al, 2012;Hancock et al, 2012;Verdier et al, 2012;Cheynier et al, 2013;Harding et al, 2013;Mouradov and Spangenberg, 2014;Pérez-Díaz et al, 2014;Zhou et al, 2015;Zhu et al, 2015;Chezem and Clay, 2016).…”
Section: Roles Of Tannins In Plants and Challenges To Harnessing Theimentioning
confidence: 99%
“…All enzymes involved in the biosynthesis of the CT building blocks (i.e., flavan-3-ols) have been identified, apart from the elusive final condensing enzyme(s) (Harding et al, 2013). Two genes and several myeloblastosis (MYB) transcription factors (i.e., proteins with myeloblastosis DNAbinding domains that regulate CT synthesis) are responsible for the production of two of the flavan-3-ols (i.e., catechin and epicatechin; Ferreyra et al, 2012;Cheynier et al, 2013;Zhu et al, 2015;Chezem and Clay, 2016), but the genes and transcription factors for the other flavan-3-ols await identification. The MYB transcription factors from barrelclover (Medicago truncatula Gaertn.)…”
Section: Tannin Variation In Germplasm Collections and Potential Formentioning
confidence: 99%
“…For example, in Arabidopsis an MBW complex including WEREWOLFE, GLABRA3 (GL3), and Transparent Testa Glabra (TTG) controls the transcription of GLABRA2 (GL2), a TF, which acts on root and trichome developmental programs (Rerie et al, 1994;Bernhardt et al, 2005). Recently it was suggested that MBW complexes controlling secondary metabolism may have evolved from similar MBW complexes that regulate more ancient gene networks for differentiation of cell types (Chezem and Clay, 2016).…”
mentioning
confidence: 99%
“…In this study, the promoter motif analysis of CYP83B1 gene showed that a G-box-like sequence CACCTG is present at the position −120 to −125. It has been previously reported that AC-rich sequences, such as ACC[A/T]A[A/C][T/C] and ACC[A/T][A/C/T][A/C/T], are typical motifs important for binding R2R3-MYB TFs (Prouse and Campbell, 2012; Chezem and Clay, 2016). Here, we showed that MYB51 directly binds to the AC-rich sequence ACCAACC at the position −95 to −101, similarly to the way that ZmMYB31 binds the maize lignin gene promoters containing the ACC(T/A)ACC consensus sequence (Fornalé et al, 2010).…”
Section: Discussionmentioning
confidence: 99%